IMPLIKASI ALIRAN PROGRESIVISME DALAM PENDIDIKAN ISLAM DI ERA DIGITAL - Salwa, Najwa Manikha; Prasetya, Valerina Eka; Prilliano, Brian; Bakar , M. Yunus Abu (Cahaya Ilmu Bangsa Institute, 2024)
This article examines the implications of the progressive education movement in Islamic education in the digital era, focusing on the integration of technology in the learning process. Progressive education, which emphasizes student-centered learning and innovation, offers new opportunities to enhance the learning experience amidst rapid technological advancements. Therefore, the application of progressive principles in digital education needs to be aligned with Islamic principles, such as the importance of balancing intellect and heart, as well as the holistic development of individual potential. This article also explores how digital technology can be effectively utilized to enrich the learning process without neglecting the spiritual and ethical values embedded in Islamic teachings. The implications of this study suggest that education in the digital era must be able to integrate technology with religious values, thereby producing a generation that is not only intellectually capable but also possesses good character in accordance with Islamic teachings. The researcher employs a library research method to gather and analyze various relevant literature sources, including books, journal articles, theses, and official documents discussing progressive education, Islamic education, and the use of technology in education. Artikel ini mengkaji implikasi aliran progresivisme dalam pendidikan Islam di era digital, dengan fokus pada integrasi teknologi dalam proses pembelajaran. Progresivisme pendidikan, yang menekankan pada pembelajaran yang berpusat pada siswa dan inovasi, menawarkan peluang baru untuk meningkatkan pengalaman belajar di tengah perkembangan teknologi yang pesat. Oleh karena itu, penerapan prinsip-prinsip progresivisme dalam pendidikan digital perlu disesuaikan dengan prinsip-prinsip Islam, seperti pentingnya keseimbangan antara akal dan hati, serta pengembangan potensi individu secara holistik. Artikel ini juga mengeksplorasi bagaimana teknologi digital dapat digunakan secara efektif untuk memperkaya proses pembelajaran tanpa mengabaikan nilai-nilai spiritual dan etika yang terkandung dalam ajaran Islam. Implikasi dari kajian ini menunjukkan bahwa pendidikan di era digital harus mampu mengintegrasikan teknologi dengan nilai-nilai agama, sehingga dapat menghasilkan generasi yang tidak hanya cerdas secara intelektual tetapi juga memiliki karakter yang baik sesuai dengan ajaran Islam. Peneliti menggunakan metode library research untuk mengumpulkan dan menganalisis berbagai sumber literatur yang relevan, termasuk buku, artikel jurnal, tesis, dan dokumen resmi yang membahas progresivisme pendidikan, pendidikan Islam, serta penggunaan teknologi dalam pendidikan.